The Relationship between Diabetes Burnout Syndrome and Complication Prevention Behavior in Diabetes Mellitus Patients - Lutfi Wahyuni; Umi Azizah Kusumaningrum (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2026)
One of the diseases that often occurs among the public is diabetes mellitus, a chronic condition that can cause worsening problems throughout the patient's life due to metabolic disorders that occur in the pancreas. Diabetes sufferers often experience stress, anger, despair, frustration, and emotional disturbances called diabetes burnout. This study aims to determine the relationship between diabetes distress and The Relationship between Diabetes Burnout Syndrome and Complication Prevention Behavior in Diabetes Mellitus Patients diabetes sufferers. This type of research uses a quantitative method, with a retrospective approach. The instrument used in this study was a questionnaire that had been tested for validity in previous studies. Respondents were 66 diabetes sufferers at the Bangsal Community Health Center (UPT Bangsal), selected using a total sampling technique. The results of the analysis using the Spearman rho correlation test obtained a p-value of 0.000, indicating a relationship between diabetes distress and self-care in diabetes sufferers at the Bangsal Community Health Center (UPT Bangsal). The correlation coefficient value of -0.649 indicates a strong closeness with a negative direction, meaning that the milder the diabetes burnout, the better the Complication Prevention Behavior in Diabetes Mellitus Patients